Breathing–Swallowing Discoordination and Inefficiency of an Airway Protective Mechanism Puts Patients at Risk of COPD Exacerbation - Yoshimatsu Y; Tobino K; Nagami S; Yagi N; Oku Y (International Journal of COPD, 2020)
Yuki Yoshimatsu, 1, 2 Kazunori Tobino, 1, 3 Shinsuke Nagami, 4 Naomi Yagi, 2, 5, 6 Yoshitaka Oku 2 1Department of Respiratory Medicine, Iizuka Hospital, Iizuka, Fukuoka, Japan; 2Department of Physiology, Hyogo College of Medicine, Nishinomiya, Hyogo, Japan; 3Department of Respiratory Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 4Department of Speech Language Pathology and Audiology, Faculty of Rehabilitation, Kawasaki University of Medical Welfare, Kurashiki, Okayama, Japan; 5Department of Neurology, Graduate School of Medicine, Kyoto University, Kyoto, Japan; 6Department of Medical Engineering, Himeji Dokkyo University, Himeji, Hyogo, JapanCorrespondence: Yuki YoshimatsuDepartment of Respiratory Medicine, Iizuka Hospital, Iizuka, Fukuoka 820-8505, JapanTel +81-948-22-3800Fax +81-948-29-5744Email yukitsukihana0105@gmail.comIntroduction: Dysphagia is a newly acknowledged multifactorial risk factor for the exacerbation of chronic obstructive pulmonary disease (COPD). Effective screening methods are awaited. We performed a prospective study to evaluate the impact of musculature and breathing–swallowing discoordination on the exacerbation of COPD with a novel swallowing monitor using a piezoelectric sensor.Patients and Methods: This was the second part of a prospective study of patients with COPD from the Iizuka COPD cohort. Seventy patients with stable COPD underwent dysphagia screening, skeletal muscle mass index (SMI) and tongue pressure measurements, and swallowed 3 mL and 30 mL of water while wearing a swallowing monitor. Patients were followed for one year.Results: During the follow-up period, 28 patients experienced exacerbations (E group), and 42 had none (non-E group). There was no significant difference in tongue pressure measurements between the two groups. The SMI in the E group was significantly lower than that in the non-E group. Among the swallowing monitor measurements, the 3 mL I-SW% (the percentage of swallows in which inspiration preceded the swallow [out of ten 3 mL swallows]) was significantly lower in the E group than in the non-E group.Conclusion: Breathing–swallowing coordination is an independent factor related to the exacerbation of COPD. Not only the presence of discoordination but also the inability to produce an airway protection mechanism may contribute to more frequent aspiration and exacerbations.Keywords: dysphagia, screening, aspiration, piezomonitor, inspiration, COPD